A Single Nutristep™ Question as a Food Insecurity Screening Tool. (1st June 2016) - Borkhoff, CM; Bayoumi, I; Nurse, KM; Chen, Y; Maguire, JL; Parkin, PC; Birken, C
Abstract: BACKGROUND: Food insecurity could pose serious health risks, deficiencies, and be harmful to early children's healthy growth and development. Many family health teams use the Nutrition Screening Tool for Every Preschooler (NutriSTEP™) as a tool to provide a fast, valid way to assess the eating habits of toddlers and preschoolers and identify individual kids at risk. Furthermore, the NutriSTEP™ questionnaire is being rolled out in Public Health Units in Ontario. OBJECTIVES: The objectives of this study were to assess the criterion and construct validity of the 1-item on the NutriSTEP™ questionnaire: "I have difficulty buying food I want to feed my child because food is expensive" for measuring food insecurity. DESIGN/METHODS: A cross-sectional study of healthy children, aged 18 months to 5 years, seen for primary care between June 2008 and January 2015 was conducted through the TARGet Kids! practice-based research network. A parent of each participant completed the NutriSTEP™ questionnaire for toddlers aged 18–35 months or for children aged 3–5 years. Parents also responded to the 2-item Food Insecurity Screen (which comes from the 18-item Household Food Security Survey). Criterion validity was evaluated by comparing the responses of the 1-item NutriSTEP™ to the 2-item FI Screen as a gold standard and testing the sensitivity, specificity, and likelihood ratios for a positive and negative result. Convergent validity (the correspondence between the 1-item screen and theoretically related variables) was assessed with multivariable logistic regression. RESULTS: 1174 children (mean age 37 months) were included: 53 (4.5%) children were categorized as food insecure. An affirmative response to the 1-item NutriSTEP™ had a sensitivity of 84.9% (95% CI: 72.4-93.3) and a specificity of 91.2 % (95% CI: 89.4- 92.8). A positive or food insecure NutriSTEP™ response is 9.6 times more likely to occur in a participant with a food insecure response than a food secure response to the FI Screen. A negative or food secure NutriSTEP™ response is 6 times less likely to occur in a participant with a food insecure response than a food secure response to the FI Screen. An affirmative response to the 1-item NutriSTEP™ was associated with increased odds of a low self-reported after-tax annual household income of 0 - 29, 999 (adjusted odds ratio [aOR]: 7.6; (95% CI: 89.4- 92.8); P<0.001). CONCLUSION: Children who were food insecure were identified with the 1-item NutriSTEP™, suggesting that this single question may be an effective screening tool for food insecurity.